Evaluating Sisal Fiber-Reinforced Gypsum Composites for Water Absorption and Mechanical Performance - Kidane Hadgu Asefa; Temesgen Abrha Tkue; Temesgen Berhanu Yallew (Advances in Materials Science and Engineering)
There has been a great research interest for investigation of new construction materials which can reduce environmental impact and cost, with improved structural performance. Recently, sisal fiber is being used as a reinforcement material in the development of reinforced composites. Here, sisal fiber-gypsum reinforced composites were prepared using the hand lay-up method followed by the compression technique. The effects of weight percentage (Wt. %) of the sisal fiber reinforcement on the mechanical properties of the developed sisal fiber-gypsum composites were investigated experimentally by varying the Wt. % as 5, 10, and 15%. The mechanical properties were tested as per the ASTM standards. The results revealed that the long unidirectional sisal fiber-gypsum composites exhibited higher impact and hardness strengths with lower water absorption behaviour than the short-chopped sisal fiber-gypsum composites. In addition, the impact strength increased with increase in Wt. % for both short-chopped and long unidirectional sisal fiber reinforcement. While the hardness strength decreased with increase in Wt. % for both short-chopped and long unidirectional sisal fiber. The experimental investigation has established sisal fiber as an important reinforcement material for improving the performance of the neat gypsum in a wide range of architectural applications such as ceilings, decorative partitions, and light covers.